2012
DOI: 10.1016/j.jacc.2012.08.1006
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Change in Biomarkers of Myocardial Stress and Injury, and Subsequent Heart Failure Risk in Older Adults

Abstract: Objectives The aim of this study was to evaluate the association between physical activity and changes in levels of highly sensitive troponin T (cTnT) and N-terminal pro–B-type natriuretic peptide (NT-proBNP), and the subsequent risk of the development of heart failure (HF) in community-dwelling older adults. Background Higher baseline levels of cTnT and NT-proBNP and increases over time correlate with the risk of HF in older adults. Factors modifying these levels have not been identified. Methods NT-proBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 35 publications
1
72
2
Order By: Relevance
“…49 Furthermore, in the CHS (Cardiovascular Health Study), it was shown that physical activity decreased the likelihood for an increase in NT-proBNP and hs-troponin over time, and this was associated with a lower risk of new-onset HF. 50 …”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…49 Furthermore, in the CHS (Cardiovascular Health Study), it was shown that physical activity decreased the likelihood for an increase in NT-proBNP and hs-troponin over time, and this was associated with a lower risk of new-onset HF. 50 …”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…39 Physical activity may prevent cardiac injury and neurohormonal activation and thereby decrease the risk of HF. 40 Excessive sedentary behavior is also associated with unfavorable cardiovascular risk factors. 17 Animal and prolonged human bed rest studies suggest that inadequate muscle contraction may suppress skeletal muscle lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In contrast, the role of PA in reducing risk of HF has not been emphasized in existing guidelines and public health recommendations. 15 Although observational cohort studies have reported an inverse association between higher levels of PA and HF risk, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] a comprehensive assessment of the quantitative dose-response association between PA and HF risk has not been previously reported. Understanding this relationship is important because recent studies suggest that there may be important differences in the mechanisms through which PA modifies HF risk and CHD risk, 20 and the dose of PA needed to significantly lower HF risk may differ from that currently recommended to reduce CHD risk.…”
Section: Editorial See P 1777 Clinical Perspective On P 1794mentioning
confidence: 99%